Architecting modern data platforms : a guide to enterprise Hadoop at scale - Kunigk, Jan; Buss, Ian; Wilkinson, Paul; George, Lars (O'Reilly Media, 2018)
There's a lot of information about big data technologies, but splicing these technologies into an end-to-end enterprise data platform is a daunting task not widely covered. With this practical book, you'll learn how to build big data infrastructure both on-premises and in the cloud and successfully architect a modern data platform. Ideal for enterprise architects, IT managers, application architects, and data engineers, this book shows you how to overcome the many challenges that emerge during Hadoop projects. You'll explore the vast landscape of tools available in the Hadoop and big data realm in a thorough technical primer before diving into: Infrastructure, Platform and Taking Hadoop into the cloud.